Modern methods of using folk proverbs in the process of educating elementary school students - Maxbuba Jumayeva Soatmurod qizi; Azimova Dilfuza (Genius Journals, 2023)
This article contains information about the use of folklore in the education of primary school students, moral education of students
Keywords: folk art; education; proverb